2017
DOI: 10.1186/s13104-017-2695-5
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial bacterial infections and their antimicrobial susceptibility patterns among patients in Ugandan intensive care units: a cross sectional study

Abstract: BackgroundThe intensive care unit (ICU) admits critically ill patients requiring advanced airway, respiratory, cardiac and renal support. Despite the highly-specialized interventions, the mortality and morbidity is still high due to a number of reasons including nosocomial infections, which are the most likely complications in hospitalized patients with the rates being highest among ICU patients.MethodsIn this cross-sectional study of 111 adult patients admitted to 2 of the ICUs in Uganda, we set out to descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
83
6
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 40 publications
20
83
6
4
Order By: Relevance
“…First, antimicrobial resistance is common in sub-Saharan Africa [23] and can crucially reduce the beneficial effects of antimicrobial therapy. Because antimicrobial resistance patterns for the study region were not available, we could not be sure whether antimicrobial therapy as per the study protocol was appropriate and truly effective.…”
Section: Discussionmentioning
confidence: 99%
“…First, antimicrobial resistance is common in sub-Saharan Africa [23] and can crucially reduce the beneficial effects of antimicrobial therapy. Because antimicrobial resistance patterns for the study region were not available, we could not be sure whether antimicrobial therapy as per the study protocol was appropriate and truly effective.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Agaba et al, (2017) revealed that the major isolated bacteria in nosocomial bacterial infections in Ugandan intensive care units were Klebsiella pneumoniae (30%), Acinetobacter spp. 22%, Staphylococcus aureus 14% and the MDR E. coli (50%) [5].…”
Section: Introductionmentioning
confidence: 99%
“…HAIs include diseases that can be associated with surfaces and devices present in hospitals and can spread through health care staff, contaminated surfaces or air droplets. These infections are more frequent in UTIs where outbreaks often originate [11]. HAIs increase deaths (morbidity and mortality), antimicrobial resistance, prolong the duration of hospital stays, and consequentially healthcare costs [12].…”
Section: Introductionmentioning
confidence: 99%
“…The most common pathogen causing HAIs are Clostridium difficile and ‘ESKAPE’ bacteria ( Enterococcus spp ., Staphylococcus aureus , Klebsiella spp ., Acinetobacter spp ., Pseudomonas aeruginosa , and Enterobacteriaceae) [14,15]. Many of these bacteria exhibit antimicrobial resistance and can cause infections of the bloodstream, urinary tract, severe pneumonia, and surgical site infection [11,16].…”
Section: Introductionmentioning
confidence: 99%